Overcoming Double Jeopardy: Successful Orthotopic Heart Transplant in a Recipient With Bacterial and Fungal Infections - Paopat Munthananuchat; Bundit Naratreekoon; Narongrit Kantathut; Piya Samankatiwat; Akeatit Trirattanapikul; Teerapat Yingchoncharoen (Case Reports in Cardiology)
Although active infection is generally a contraindication before an orthotopic heart transplant, a 16-year-old man diagnosed with dilated cardiomyopathy successfully underwent an orthotopic heart transplant despite having active probable invasive pulmonary aspergillosis and bacterial pneumonia in the presence of septic and cardiogenic shock.